Implementasi E-Commerce Brand Fashion VASignature Berbasis Laravel dan Midtrans dengan Evaluasi Usability Menggunakan USE Questionnaire - Imam Murtadho (JSAI (Journal Scientific and Applied Informatics), 2026)
The rapid development of information technology has encouraged businesses to transform conventional sales processes into digital-based systems to improve operational efficiency and service quality. VASignature, a local fashion brand, faces challenges in managing product data, sales transactions, and reporting processes due to the use of manual procedures. This study aims to implement an e-commerce system based on the Laravel framework integrated with the Midtrans Payment Gateway to support a more structured and automated sales process. The system was developed using the Software Development Life Cycle (SDLC) Waterfall model, which consists of requirements analysis, system design, implementation, testing, and evaluation stages. System testing was conducted using Black-box Testing to evaluate functional performance and the USE Questionnaire to assess usability based on four dimensions: Usefulness, Ease of Use, Ease of Learning, and Satisfaction. The results indicate that the developed system was successfully implemented, with all Black-box Testing scenarios achieving a 100% success rate. The usability evaluation produced scores of 88.40% for Usefulness, 90.13% for Ease of Use, 91.20% for Ease of Learning, and 89.47% for Satisfaction, resulting in an overall average score of 89.80%, which falls into the excellent category. These findings demonstrate that the proposed system not only functions effectively from a technical perspective but also provides a positive user experience and high user acceptance. Therefore, the developed e-commerce system is considered suitable for supporting digital sales operations and business management at VASignature.